Bimunasibat-i shishumin salruz-i darguzasht-i duktur Shari`ati : (s.n.])
On the sixth anniversary of Dr Shari'ati's departure, a letter from Ahmad 'Ali Baba'i to Mr Khumaini. Quoted from the Daily Jibhah.